Fuel retention in plasma facing materials of the JET ITER-like wall - Makepeace, CWK (2021)
This thesis, presents results from the Joint European Torus (JET), beryllium ITER-like wall. Isotopic hydrogen retention is investigated at three microstructurally unique sites: erosion zones, co-deposition zones, and melted material, found across the reactor at the inner and outer wall limiters and dump plate tiles. The techniques applied to these novel inservice materials were: Scanning Electron Microscopy with Energy Dispersive X-Ray (SEM-EDX), Raman Spectroscopy; Focused Ion Beam (FIB) 3D milling; Scanning Transmission Electron Microscopy (STEM) with Electron Energy Loss Spectroscopy (EELS) and Energy Dispersive X-Ray (EDX); Atom Probe Tomography and Thermal Desorption Spectroscopy (TDS).